Nurses’ Attitude About Pap Smear As An Early Screening Method For Cervical Cancer In The Private Hospital - Belet Lydia Ingrit; Martina Elfrida Sinaga; Puji Astutik; Fransiska Ompusunggu (Fakultas Keperawatan Universitas Andalas, 2020)
The prevalence of cervical cancer in Indonesia is very high, which it is estimated that every day 40-45 new cases appear. The purpose of this study was to describe nurses’ attitude about pap smear as an early detection of cervical cancer in a hospital in western Indonesia. The research method was used descriptive quantitative with purposive sampling technique. The results of this study shows that most of the respondents have the positive attitude in performing pap smears in the Western Indonesia hospitals with the percentage of 97,5% and the rest indicate negative attitude. The conclusion of this study is that the positive attitude of nurses towards early detection of pap smears is expected to be maintained and furthermore the hospital continues to provide health facilities for female nurses to carry out early detection of cervical cancer as an annual program from hospital.